2003
DOI: 10.1002/pssb.200301560
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐phase precipitation of CdTe nanoparticles in glass

Abstract: Growth of CdTe nanoparticles in glass is studied through the analysis of optical absorption spectroscopy with the help of a quantized state effective mass model. Glass includes nanoparticles with an initial size of ~1.6 nm on cooling to room temperature from the melt at ~1000 °C. Particles form by heterogeneous nucleation followed by diffusion-limited growth. The narrowest particle size dispersion of 15% is obtained for an average radius of ~2.28 nm at the end of heat treatment at 600 °C for 4.5 h. The magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…The decrease of activation energy with increasing the doping concentrations also confirms the increase in solubility of semiconductor components and increase in diffusion coefficients in our glass matrix. On the other hand this value of activation energy is very small relative to the previously reported value of CdTe in commerciall schott filters glass (SiO 2 -K 2 O-ZnO-B 2 O 3 ) which was 170 kJ/mol [13]. The annealing temperatures for the growing of nanoparticles are (310˚C -390˚C) which experienced here are less than those used for silicate glass (575˚C -675˚C).…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…The decrease of activation energy with increasing the doping concentrations also confirms the increase in solubility of semiconductor components and increase in diffusion coefficients in our glass matrix. On the other hand this value of activation energy is very small relative to the previously reported value of CdTe in commerciall schott filters glass (SiO 2 -K 2 O-ZnO-B 2 O 3 ) which was 170 kJ/mol [13]. The annealing temperatures for the growing of nanoparticles are (310˚C -390˚C) which experienced here are less than those used for silicate glass (575˚C -675˚C).…”
Section: Resultscontrasting
confidence: 58%
“…CdTe is one of the II-VI semiconductor nanocrystals which have a large exciton Bohr diameter ~15 nm, and therefore it offers the possibility of studying quantum confinement effects in higher cluster size regimes. Up to now very rare work are published about the glass matrices doped with CdTe nanocrystals [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…2 Experimental CdSe 1-x Te x nanocrystals were grown in a borosilicate glass using a conventional solid-state precipitation technique, generally similar to the one described in [26,27]. The nanocrystal growth was carried out at thermal treatment for 2 to 12 h, the temperature ranging from 625 to 700 °C.…”
mentioning
confidence: 99%
“…The stoichiometry remains unchanged with heat treatment during growth because it is observed that the two-peak structure does not shift in wave number. The growth kinetics of CdTe nanoparticles in glass prepared by a single heat-treatment process has been published elsewhere [17].…”
Section: Methodsmentioning
confidence: 99%